Deteritorialisasi dan Reteritorialisasi Kursi Tamu di Bangsal Prabayaksa Keraton Kasepuhan Cirebon - Maugina Rizki Havier; Imam Santosa; Achmad Haldani Destiarmand (Aliansi Desainer Produk Industri Indonesia (ADPII), 2026)
The phenomenon of deterritorialization in the context of palace interiors constitutes a significant aspect that reflects the dynamic shift in material cultural identity, as exemplified by the guest chair in the Prabayaksa Pavilion of the Kasepuhan Palace, Cirebon. This furniture object demonstrates a process of detachment from its original meaning as a representation of the European Veranda Chair style, followed by the formation of a new identity within the symbolic framework of the palace. Drawing on Gilles Deleuze and Félix Guattari’s theory of deterritorialization and reterritorialization, this study examines how furniture as a material object undergoes shifts in meaning and function within a local power space. While the architectural, cosmological, and territorial aspects of the palace have been widely studied, research on the interior—particularly furniture as a means of constructing visual and cultural identity—remains limited. Therefore, this research is urgent in addressing the gap within historical interior studies, especially furniture analysis grounded in contemporary theory. This study employs a qualitative approach, using the ethnomorphological method, which combines ethnographic observation with morphological analysis to explore the form, structure, colour, and material of the chair. The findings reveal that the guest chair underwent a process of deterritorialization from its European colonial identity and reterritorialization as a symbolic artefact embedded within the identity of the Kasepuhan Palace. Thus, the chair functions not only as an interior element but also as a medium of representation for royal power and cultural continuity within the sacred space of the palace.